(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1854)
The author presents his argument regarding the extent of Brittonic territory in Roman-age Scotland. He compares the names of tribes recorded in Ptolemy’s Geography to similar tribal names recorded in southern parts of Britain and concludes that there is significant overlap for tribal names in the central belt, as well as the areas that are now Fife, Perthshire and Angus. He also supports his argument with evidence from contemporary place-names, particularly the use of the prefix ’aber’, that he argues is imported from Brittonic areas such as Wales rather than Gaelic-speaking Ireland. Rhind summarises his argument through using tables and lists at the end of the article. Meeting notes for the meeting held 13 June 1853 are appended.